Transformation of Social Interaction in the Digital Age: Impact, Challenges, and Prospects of Technology in Social Relationships - Yıldız, Deniz; Nur, Zeynep (Bulletin of Science, Technology and Society, 2024)
The development of digital technology has brought about fundamental changes in the pattern of social interaction in the modern era. Technology allows communication to be faster, wider and more efficient, but it also poses challenges in maintaining the quality of authentic social relationships. This research aims to analyze how technology affects social interactions, the negative impact it has on interpersonal relationships, and the role of technology in shaping social relationships in the future. Literature study is used as the research approach by reviewing various academic sources from reputable international journals. The results show that digital technology has accelerated communication, but also reduced emotional depth in social interactions. Dependence on digital communication leads to decreased social skills, increased social isolation, and the formation of information bubbles that narrow individuals' social horizons. Artificial intelligence algorithms, virtual reality and social media are expected to further shape the dynamics of social relationships in the future, potentially strengthening connectedness but also increasing social fragmentation. To optimize the role of technology in social relations, policies are needed that encourage a balance between digital and in-person interactions. Digital education as well as technology design that supports deeper social engagement can help maintain the quality of interpersonal relationships. With the right approach, technology can remain a tool that enriches social relationships without sacrificing the essence of deep emotional connections